2011
DOI: 10.1162/jocn.2010.21579
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Improves Word Retrieval in Healthy and Nonfluent Aphasic Subjects

Abstract: A number of studies have shown that modulating cortical activity by means of transcranial direct current stimulation (tDCS) affects performances of both healthy and brain-damaged subjects. In this study, we investigated the potential of tDCS to enhance associative verbal learning in 10 healthy individuals and to improve word retrieval deficits in three patients with stroke-induced aphasia. In healthy individuals, tDCS (20 min, 1 mA) was applied over Wernicke's area (position CP5 of the International 10-20 EEG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
212
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(230 citation statements)
references
References 42 publications
12
212
1
5
Order By: Relevance
“…So far, there is growing evidence that the integrity and strength of spontaneous functional connectivity in several networks are of behavioral and cognitive relevance (Massimini et al, 2005;Hampson et al, 2006;He et al, 2007;Schacter et al, 2007;Kelly et al, 2008;Schilbach et al, 2008;Lewis et al, 2009;Ferrarelli et al, 2010;Wirth et al, 2011). Thus, our findings may explain why a wide range of cognitive domains has already been successfully modulated by prefrontal tDCS Sparing et al, 2008;Cerruti and Schlaug, 2009;Dockery et al, 2009;Elmer et al, 2009;Fertonani et al, 2010;Hecht et al, 2010;Ambrus et al, 2011;Fiori et al, 2011). Within this range of cognitive domains, we have recently shown that prefrontal tDCS using similar stimulation parameters as in the current study, led to an improvement of working memory performance (n-back) associated with changes in EEG activity patterns (Keeser et al, 2011).…”
Section: Effects Of Tdcs On Rsnsmentioning
confidence: 60%
See 1 more Smart Citation
“…So far, there is growing evidence that the integrity and strength of spontaneous functional connectivity in several networks are of behavioral and cognitive relevance (Massimini et al, 2005;Hampson et al, 2006;He et al, 2007;Schacter et al, 2007;Kelly et al, 2008;Schilbach et al, 2008;Lewis et al, 2009;Ferrarelli et al, 2010;Wirth et al, 2011). Thus, our findings may explain why a wide range of cognitive domains has already been successfully modulated by prefrontal tDCS Sparing et al, 2008;Cerruti and Schlaug, 2009;Dockery et al, 2009;Elmer et al, 2009;Fertonani et al, 2010;Hecht et al, 2010;Ambrus et al, 2011;Fiori et al, 2011). Within this range of cognitive domains, we have recently shown that prefrontal tDCS using similar stimulation parameters as in the current study, led to an improvement of working memory performance (n-back) associated with changes in EEG activity patterns (Keeser et al, 2011).…”
Section: Effects Of Tdcs On Rsnsmentioning
confidence: 60%
“…Anodal tDCS of the dorsolateral prefrontal cortex (DLPFC) with the cathode placed over the contralateral supraorbital region has been found to improve performance in several cognitive domains, including executive functions, verbal skills, and memory performance in healthy subjects (Iyer et al, 2005;Wassermann and Grafman, 2005;Cerruti and Schlaug, 2009;Sparing et al, 2008;Dockery et al, 2009;Fiori et al, 2011), as well as in patients with Parkinson's disease and stroke Jo et al, 2009). Promising pilot data suggest a positive therapeutic effect in patients with major depression Boggio et al, 2008;Rigonatti et al, 2008;Ferrucci et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fridriksson et al (2011) applied the same procedure used by Baker et al (2010) in eight left-brain-damaged patients with chronic fluent aphasia, and showed that anodal tDCS administered during language treatment decreased verbal reaction times during naming, as assessed immediately post-treatment and 3 weeks later. Another recent study (Fiori et al, 2011) highlights the beneficial effects of 5 days of anodal tDCS in three aphasic patients. The stimulation was applied to Wernicke's area while patients were executing a naming task.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in chronic aphasia patients, non-invasive brain stimulation has been shown to increase the number of correct responses and to reduce response times. Moreover, recent studies suggest that these effects can persist over time (Baker et al, 2010;Fiori et al, 2011;Floel et al, 2011;Fridriksson et al, 2011;Hamilton et al, 2010;Kakuda, Abo, Uruma, et al, 2010b;Martin, Naeser, Ho, Doron, et al, 2009;Martin, Naeser, Ho, Treglia, et al, 2009;Naeser, Martin Lundgren, et al, 2010;Naeser, Martin Nicholas, Baker, Seekins, Helm-Estabrooks, et al, 2005;Naeser, Martin, Nicholas, Baker, Seekins, Kobayashi, et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…tDCS has been shown to successfully improve various perceptual or cognitive abilities both in healthy participants and in patients, and when administered either with (Looi, Duta, Brem, Huber, Nuerk & Cohen Kadosh, 2016) or without a concurrent training (Coffman, Clark & Parasuraman, 2014). In particular, tDCS has been found to improve functions such as working memory (Andrews, Hoy, Enticott, Daskalakis & Fitzgerald, 2011;Fregni, Boggio, Nitsche, Bermpohl, Antal, Feredoes, Marcolin, Rigonatti, Silva, Paulus & Pascual-Leone, 2005), long-term memory (Marshall, Molle, Hallschmid & Born, 2004;Sandrini, Brambilla, Manenti, Rosini, Cohen & Cotelli, 2014), language (Fertonani, Rosini, Cotelli, Rossini & Miniussi, 2010;Fiori, Coccia, Marinelli, Vecchi, Bonifazi, Ceravolo, Provinciali, Tomaiuolo & Marangolo, 2010;Monti, Cogiamanian, Marceglia, Ferrucci, Mrakic-Sposta, Vergari, Zago & Priori, 2008;Pisoni, Papagno & Cattaneo, 2012;Ross, McCoy, Wolk, Coslett & Olson, 2010;Sparing, Dafotakis, Meister, Thirugnanasambandam & Fink, 2008), visual and attentional skills (Antal, Nitsche, Kruse, Kincses, Hoffmann & Paulus, 2004;Bolognini, Fregni, Casati, Olgiati & Vallar, 2010;Kraft, Roehmel, Olma, Schmidt, Irlbacher & Brandt, 2010;Ding, Li, Spiegel, Chen, Chan, Luo, Yuan, Deng, Yu & Thompson, 2010). However, efficacy of tDCS has recently been disputed (e.g.…”
Section: Introductionmentioning
confidence: 99%